Impaired Emotional Self-Referential Processing in First-Episode Schizophrenia - Zhao, Yanli; Wang, Zhiren; Zhang, Yueyao; Zhang, Yuanyuan; Zhang, Jinguo; Li, Dong; Xiao, Chunling; Tan, Shuping; Zhang, Dandan (Frontiers in Psychiatry, 2021)
Impairments in self-representation are relevant to the expression of psychosis. To date, the characteristics and neural mechanisms of self-impairment in schizophrenia remain unclear. To this end, we used event-related potentials (ERPs) to measure brain activity in 56 first-episode patients with schizophrenia and 56 healthy controls. Participants judged personal trait adjectives regarding themselves, their mothers, or a public person, followed by an unexpected old/new recognition test. The recognition score for mother-reference adjectives was lower than that for self-reference adjectives in patients, while the control group showed comparatively high recognition scores for both self- and mother-referential adjectives. In addition, control subjects recognized more negative words, while patients remembered more positive words. ERP data revealed that controls exhibited typical task effects (self-reference = mother-reference > other-reference) during both automatic attention and effortful encoding periods [indexed by P2 and the late positive potential (LPP), respectively]. In contrast, patients only exhibited the task effect in the P2 amplitude. Moreover, controls exhibited larger P2 amplitudes during encoding negative than positive words, whereas patients had enhanced LPP amplitudes during memory retrieval of positive compared to negative words. These findings demonstrated self-representation dysfunction in first-episode schizophrenic patients in mother (the intimate other) referential processing and the absence of a negative memory bias.